Pregunta
Score: \( 8 / 10 \) Penalty: none Question If \( D=1+4 p-6 p^{2} \) and \( C=1-p \), find an expression that equals \( 2 D-3 C \) in standard form. Answer Attempt 1 out of 2 Show Examples Watch video
Ask by Joseph Beck. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( 2D - 3C = -12p^{2} + 11p - 1 \)
Solución
To find an expression that equals \( 2D - 3C \) in standard form, follow these steps:
### Given:
\[
D = 1 + 4p - 6p^{2}
\]
\[
C = 1 - p
\]
### Step 1: Substitute \( D \) and \( C \) into \( 2D - 3C \)
\[
2D - 3C = 2(1 + 4p - 6p^{2}) - 3(1 - p)
\]
### Step 2: Distribute the constants into each expression
\[
= 2 \cdot 1 + 2 \cdot 4p + 2 \cdot (-6p^{2}) - 3 \cdot 1 + 3 \cdot p
\]
\[
= 2 + 8p - 12p^{2} - 3 + 3p
\]
### Step 3: Combine like terms
- **Constant terms:** \( 2 - 3 = -1 \)
- **\( p \) terms:** \( 8p + 3p = 11p \)
- **\( p^{2} \) terms:** \( -12p^{2} \)
### Step 4: Write the expression in standard form
\[
2D - 3C = -12p^{2} + 11p - 1
\]
### Final Answer:
\[
2D - 3C = -12p^{2} + 11p - 1
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Bonus Knowledge
To find the expression that equals \( 2D - 3C \), we start by substituting the given expressions for \( D \) and \( C \). First, calculate \( 2D \): \[ D = 1 + 4p - 6p^2 \\ 2D = 2(1 + 4p - 6p^2) = 2 + 8p - 12p^2 \] Next, calculate \( -3C \): \[ C = 1 - p \\ -3C = -3(1 - p) = -3 + 3p \] Now we combine \( 2D \) and \( -3C \): \[ 2D - 3C = (2 + 8p - 12p^2) + (-3 + 3p) \\ = 2 - 3 + 8p + 3p - 12p^2 \\ = -1 + 11p - 12p^2 \] Thus, the expression \( 2D - 3C \) in standard form is: \[ -12p^2 + 11p - 1 \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium